Development of a general-purpose of voice-based interaction system for robots and vehicles - Tsui, Siu Ming (2019)
This report documents and present the results of a study in the development of a speech recognition incorporated system generally for robots and vehicle. The development includes the available speech recognition technologies, different techniques that are commonly used for converting speech to text and their advantages and limitations. Discussion on the suitable hardware, down to the selection of hardware. Describe segment of the Python language used as a tool to implement the system and explain the structure of the library functions.